Correlation Analysis between Macular Choroidal Thickness and Visual Field Mean Defect in Primary Open-Angle Glaucoma - Fan Li; Yiming Huo; Lihua Ma; Guangxian Tang (Journal of Ophthalmology)
Purpose. To evaluate the differences in macular choroidal thickness and volume between patients with primary open-angle glaucoma (POAG) and healthy controls to assess the correlation between macular choroidal thickness and visual field mean defect (MD). Methods. Case-control study. A total of 101 patients (101 eyes) with POAG who were hospitalized in our hospital and 102 healthy subjects (102 eyes) matched by age, sex, and axial length were consecutively selected as the POAG group and the control group, respectively. The macular choroidal thickness and volume in nine regions were measured in all subjects by enhanced-depth imaging optical coherence tomography (EDI-OCT). Results. The mean thicknesses of the choroid in the macular area in the POAG group and healthy group were 207.97 ± 62.83 µm and 208.24 ± 47.97 µm, and the mean volumes were 0.63 ± 0.19 µm3 and 0.64 ± 0.14 µm3. There were no significant differences in macular choroidal thickness, volumes of various macular regions, or mean choroidal thickness or volume between the POAG and healthy groups (all p>0.05). The macular choroidal thickness of various macular regions was not correlated with visual field MD in the POAG group (all p>0.05). Conclusion. The macular choroidal thicknesses and volumes in POAG patients were not significantly different from those in healthy individuals. The macular choroidal thickness was not correlated with MD in POAG patients. Therefore, macular choroidal thickness is not an appropriate parameter to evaluate damage caused by POAG, and the role of the macular choroid thickness in POAG needs to be further investigated.